Analisis Nilai-Nilai Sosial dalam Novel Warung Bujang Karya Jessica Carmelia - Putri Angkoso Lestari; Yundi Fitrah; Ade Bayu Saputra (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study aims to describe the social values ​​contained in the novel Warung Bujang by Jessica Carmelia. This study uses a qualitative descriptive method with a sociology of literature approach. The research data are in the form of words, sentences, dialogues, and paragraphs containing social values ​​in the novel. The main data source is the novel Warung Bujang by Jessica Carmelia, published in 2023. Data collection techniques were carried out through thorough reading, recording, and classifying data relevant to the research focus. Data analysis techniques were carried out by identifying, describing, interpreting, and concluding social values ​​based on Zubaedi's theory. The results of the study show that the novel Warung Bujang contains various social values, namely the values ​​of family, loyalty, mutual assistance, cooperation, caring, responsibility, justice, tolerance, and empathy. These values ​​are reflected through the behavior of the characters, conflicts, and social interactions that depict community life realistically. Thus, the novel Warung Bujang functions not only as a work of entertainment literature, but also as a means of learning social values ​​relevant to community life.